Structural Classification of Compounds Formed with Arabic Words and Prepositions, Not Used in Arabic in Turkish Dictionary - Sevsen Abuhannoud Büyük (Türkiyat Mecmuası)
Word derivation activities in the language are a factor that protects and ensures the development of the language. People have enriched their language in terms of expression by deriving words. The Turks, especially in the Ottoman Period, have rapidly increased the expressive power of the language and derived new words and combinations. At that time, many words gained new meanings, changed their meanings and sound, or were combined with the other foreign words and used in a new composition, especially by quoting from Arabic and Persian. In addition, new compounds not used in Arabic were derived from Arabic elements. Such as Adedimürettep (Ar. aded + Ar. mürettep), galatıhis (Ar. galat + Ar. his) and hâlihazır (Ar. hâl + Ar. hazır). In this study, the compositions formed with the Arabic elements in the last edition of the Turkish Dictionary of TDK will be examined. In this study, these compositions will be analyzed semantically and structurally under three main classifications: compositions formed according to Arabic possessive construct, compositions formed according to Persian possessive construct and compositions formed without the possessive construct. Compiled compositions will be examined in Turkish dictionaries prepared in different centuries. Compositions will also be explored in Persian and Arabic dictionaries. At the end of the study, it will be determined according to which possessive construct the compositions formed with Arabic elements in Turkish Dictionary are established in Turkish. Then, the actual meanings of the words in which the compositions are formed and their meanings in Turkish dictionaries will be explained, and the meaning change, if any, will be determined. In the study, by giving the Arabic equivalents of the compounds derived in Turkish will be tried to explain whether it is related to each other.